The Influence Of The Modern Islamic Education Movement On The Development Of Islamic Thought In Indonesian The Perspective Of The Quran (Study Of Al-Qur'an Letter Ar-Ra'd Verse 11) - Aslihah, Aslihah; Wasehudin, Wasehudin (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2023)
This discussion will talk about the organic link between the modern Islamic movement in Indonesia and the development of Islamic thought as we are witnessing it today in Indonesia. So to sequence our analysis, we will talk about modern Indonesian Islamic movements from a historical perspective, contemporary Islamic thought: a creative struggle to create a new Islamic tradition in Indonesia, at the end we include an analysis of challenges and challenges. the opportunity to create a new tradition is the study of the Qur'an letter Ar-Ra'd verse 11, in the form of literature relevant to the research topic. The author reads various books, journal articles, and publications related to the Modern Islamic Education Movement in Indonesia on the Development of Islamic Thought in Indonesia Today in the Perspective of the Qur'an. Talking about Islamic Movement Studies is an interesting thing and often invites a lot of debate. It does not only concern theoretical issues but also concerns the applicable realm in the social life of religion. The problem of studying Islamic movements, especially Islam, is experiencing dynamics and challenges according to the development of science. Keywords: Modern Islamic Movements, Historical Perspectives and Contemporary Thought